2015
DOI: 10.2147/dddt.s89505
|View full text |Cite
|
Sign up to set email alerts
|

Bu-Shen-Ning-Xin Decoction ameliorated the osteoporotic phenotype of ovariectomized mice without affecting the serum estrogen concentration or uterus

Abstract: IntroductionBu-Shen-Ning-Xin Decoction (BSNXD), a traditional Chinese medicinal composition, has been used as a remedy for postmenopausal osteoporosis, but its effects on bone metabolism and the uterus have not been reported.PurposeWe aimed to determine the respective effects of BSNXD on the bones and the uterus of ovariectomized (OVX) mice to evaluate the efficacy and safety of this herbal formula.Materials and methodsPostmenopausal osteoporosis animal models that were generated by ovariectomy were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…In addition, the enhancement of the body weight in OVX mice is due to fat body fat accumulation caused by estrogen deficiency [ 36 ]. In the present study, we showed that the enhancement of the body weight and atrophy of the uterus in OVX mice, which was also observed in other studies, was limited by the treatment with 17β-estradiol [ 37 , 38 , 39 , 40 ]. In the present study, the oral administration of AST for 6 weeks inhibited the increase in the body weight and atrophy of the uterus.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the enhancement of the body weight in OVX mice is due to fat body fat accumulation caused by estrogen deficiency [ 36 ]. In the present study, we showed that the enhancement of the body weight and atrophy of the uterus in OVX mice, which was also observed in other studies, was limited by the treatment with 17β-estradiol [ 37 , 38 , 39 , 40 ]. In the present study, the oral administration of AST for 6 weeks inhibited the increase in the body weight and atrophy of the uterus.…”
Section: Discussionsupporting
confidence: 89%
“…BSNXD is composed of dried Rehmannia root, common Anemarrhena rhizome, bark of Chinese Corktree, Barbary Wolfberry fruit, Chinese Dodder seed, Shorthorned Epimedium herb, Spina date seed and Oriental water plantain rhizome. These herbs are mixed together in specific quantities and proportions ( Table I ), to keep the phytochemical components as constant as possible and to maximize their pharmacological effect ( 30 ) BSNXD has been demonstrated to have beneficial effects on bone metabolism in PMO ( 30 ), but the molecular mechanism of that effect remains unclear. A previous study identified 16 molecular components in a BSNXD fingerprint analysis, including acteoside, berberine, jatrorrizine and icariin ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…These herbs are mixed together in specific quantities and proportions ( Table I ), to keep the phytochemical components as constant as possible and to maximize their pharmacological effect ( 30 ) BSNXD has been demonstrated to have beneficial effects on bone metabolism in PMO ( 30 ), but the molecular mechanism of that effect remains unclear. A previous study identified 16 molecular components in a BSNXD fingerprint analysis, including acteoside, berberine, jatrorrizine and icariin ( 30 ). In other studies, BSNXD ameliorated the loss of BMD and bone volume (BV) in OVX mice without affecting the serum estrogen concentration or uterus, suggesting that it may act as a regulator for the endocrine and immune systems and inhibit osteoclastogenesis by abrogation of RANKL-induced signaling pathways and by increasing the level of dehydroepiandrosterone ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu-Shen-Ning-Xin Decoction (BSNXD) is composed of traditional Chinese medicinal compounds that are used to treat women with PMO in clinical, and the composition of prescription, the main effective components, function of BSNXD was introduced in Table 1 (8-18). We have done many researches on the effects of BSNXD on bone, previously (19,20). BSNXD ameliorated the osteoporotic phenotype of ovariectomized mice without affecting the serum estrogen concentration or uterus (21); BSNXD modulates mesenchymal stem cell differentiation into osteoblasts (22); BSNXD inhibits osteoclastogenesis by abrogating the RANKL-induced NFATc1 and NF-κB signaling pathways through selective estrogen receptors (23); BSNXD suppresses osteoclastogenesis via increasing dehydroepiandrosterone to prevent postmenopausal osteoporosis (24).…”
Section: Introductionmentioning
confidence: 99%